Analisis Bibliometrik tentang Dampak Corporate Social Responsibility (CSR) terhadap Kinerja Keuangan Perusahaan - Judijanto, Loso; Sudarmanto, Eko; Triyantoro, Andri (Westscience Press, 2024)
This study employs bibliometric analysis to map the research landscape of Corporate Social Responsibility (CSR) over several decades. By synthesizing data from extensive academic databases, this research identifies thematic clusters, trends over time, collaboration networks, and potential future research directions within the field of CSR. The thematic analysis highlights the evolution from foundational CSR concepts to more nuanced discussions on the economic and strategic implications of CSR. Temporal trends suggest a shift towards integrating CSR into core business strategies, with an increasing focus on economic outcomes and shareholder interests. The author collaboration network reveals both dense and emergent clusters of researchers, indicating robust areas of established inquiry alongside emerging research fronts. Additionally, this study identifies underexplored areas such as the cost implications of CSR, its integration with marketing strategies, and the influence of regulatory frameworks, proposing these as vital for future research. This comprehensive overview not only maps the current state of CSR research but also directs future scholarly efforts towards areas with the potential for significant impact.